Enhancement of single-mode optical fiber quality factor-bit error rate by using uniform fiber Bragg grating - Alaa Husein Ali; Raed Khalid Ibrahim (Institute of Advanced Engineering and Science, 2022)
The properties of optical fibers transmission systems based on Bragg gratings and uniform fibers, which are discussed in detail in this paper. Two - fiber optic communication channels Bragg gratings are used, along with Optisystem software for simulations. It is widely used in a variety of optical communication systems, such as, dispersion compensators, band filters, amplifiers and in - fiber sensors or fiber grating lasers, because of its versatility. In this design, the distance has been changed from 10 km up to 100 km, as well as the input power from 2 dBm to 16 dBm, and the calculation of both the bit error rate (BER) and quality (Q) f actor at the receiver could be studied by modelling the model of a communication system and employing the syste m's most suited settings, such as fiber cable length (km) and input power (dBm).